Analysis Factors Of Liquid Waste Treatment OnLiquid Waste Processing UnitSugar Industrial (Case Study PGXYZ) - Eva Rusdiana; Mohammad Fuad Fauzul Mu’tamar; Khoirul Hidayat (Agroindustrial Technology Journal, 2020)
The Liquid waste sugar industry can cause pollution in the waters due to contamination, deoxygenationby pollutants and strong odors caused by biodegradation of waste in the form of hydrogen sulfide gas. Liquid sugar industry wastes can increase the levels of BOD (Biological Oxygen Demand), COD (Chemical Oxygen Demand), and TSS (Total Suspended Solid) in the waters so that handling of these wastes is needed. The purpose of this study is to determine the factors that influence each stage of the waste treatment process so that wastewater treatment can run effectively and efficiently. The results showed that the factors that could influence the purification of liquid waste were pH, temperature, discharge of wastewater, and active sludge content. The pH value of inlet of wastewater that can be tolerated is between 7-9 with a maximum temperature of 40ºC with a debitt of wastewater in the aeration pond a maximum of 120 m3 / hour and a condition of active sludge volume of 30-40%..